Novos palanques na contemporaneidade: as ágoras digitais - Amoêdo, Rafael Seixas de (2021)
Contemporary society is constituted, according to Castells (2017), in a dialectical structure around digital communication network. These new media are being used not only as support, but also as moments of more significant social practices, for example, in the dynamic contexts of contemporary politics. In this research, we take the context of the 2018 election in Brazil in order to verify the use of social networks as politicalelectoral platforms for campaign speeches, with emphasis on the context of the candidacy for the Amazonas State Government, in an investigation that concerns on the most voted candidates. The qualitative and bibliographic research performs an analysis anchored in a theoretical dialogue between Critical Discourse Analysis- CDA (FAIRCLOUGH, 2016 [2001/1992], 2003, 2012; FAIRCLOUGH, FAIRCLOUGH, 2012), the Social Semiotics of Multimodality (KRESS, 2010) and the Grammar of Visual Design- GVD (KRESS, van LEEUWEN, 2006 [1996]), and respectively in the analytical categories linked to the discursive event as practices: textual, discursive and social, as well as the representational, interactional and compositional meanings of multimodal theory. This research presents as corpus the selection of four multimodal texts produced in this deliberative context and published on the Facebook social network profiles of Wilson Lima and Amazonino Mendes, candidates for the Amazonas State Government. As for the methodological approach, in a first moment it will be performed a critical discourse analysis of the practices: 1) textual - describe the mode of organization of the text, this includes, the generic structure, the elements that compose it (vocabulary, modality, cohesion elements); discursive – 2) interpret the relationships established between the participants represented in the text and the participants who consume it, the relationship between various texts via contexts (production, distribution, consumption, reception), strength, coherence, as well as intertextual and interdiscursive elements, which together build the text in an interpersonal and evaluative way; and 3) social – which is important to critically reflect on the social event, identifying discursive orders, power relations, ideologies, among others. In a second moment, a dialogue is established between CDA and the categories referring to the meanings of GVD: 1) compositional - identifying the information values of the text, as well as the most salient ones; 2) interactional - how this relationship between participants was established via angles, distance, plans; and 3) representational, building a historical-discursive narrative process for each of the candidates. From the analysis of the texts, it is pointed out that the candidates made use of these digital contexts as campaign opportunities in a significant way in the election under investigation, however, still in a transitory process, especially when observing the maintenance of typical structures of the so-called "traditional politics", including culturally naturalized discourses, for example, metaphors of change, novelty, transformation, which are already recurrent figures of the political platforms. Networked campaign discourses are seeking to symbolically fit in and/or appropriate this virtualization, thus adapting to the new contemporary contexts of the new dynamics of hybrid contemporary social life.